Patients with unexplained primary infertility have similar uterine and ovarian blood flow parameters compared with fertile cases: A prospective cross-sectional study (Annals of Medical Research, 2021)
Aim: In this prospective cross-sectional study, we compared the uterine and ovarian artery blood flow parameters in patients diagnosed with unexplained primary infertility with fertile cases. Materials and Methods: Thirty female patients previously diagnosed as unexplained primary infertility aged 20-40 years were selected. The control group consisted of 30 fertile patients. To evaluate uterus and ovaries, all participants underwent ultrasonographic examination on the third day of the mestrual cycle. Also, blood samples were taken to evaluate the basal hormonal profile. Participants were re-evaluated on the 21st day of the menstrual cycle. Blood samples were taken for the measurement of progesterone level. Maximum endometrial thickness in the sagittal plane on both sides of the endometrial line was measured using transvaginal ultrasonography. Also, blood flows in uterine and ovarian arteries were measured via transvaginal Doppler ultrasonography. Resistance index and pulsatility index values in both uterine and ovarian arteries were recorded and averaged. Results: Both groups had similar clinical features and endometrial thickness values (P > 0.05). Patients with unexplained primary infertility had similar uterine and ovarian blood flow parameters compared to fertile patients (P > 0.05). There was no correlation between uterine and ovarian Doppler findings and demographic-clinical data. Conclusion: Patients with unexplained primary infertility have similar uterine and ovarian blood flow values compared with fertile patients.
Keywords: Doppler ultrasonography; ovarian artery; uterine artery; unexplained infertility